Inhibition of thermoinduced denaturation of bovine serum albumin by propoxazepam and its pharmacological consequences - Larionov, V.B.; Akisheva, A.S.; Golovenko, M.Ya.; Makarenko, O.A.; Borysyuk, I.Yu. (Reports of the National Academy of Sciences of Ukraine, 2022)
Serum albumin plays an important role in many physiological processes and has recently been shown to be directly involved in the anti-inflammatory processes. Many nonsteroidal anti-inflammatory drugs, in particular, have a protective effect against thermal denaturation of serum albumin. The aim of the work was studying of the in vitro anti-inflammatory activity of propoxazepam and a number of 1,4-benzodiazepine derivatives based on the protective effect on the stability of serum albumin under thermal denaturation. The protective effect of the compounds was expressed as IC50, physicochemical parameters were calculated using the programs ACD/Labs 12.01 and Chem Axom (Marvin Sketch 21.7). The IC50 values for diazepam and propoxazepam were found to be almost twice as high as the reference drug ibuprofen. Compounds with the free hydroxy group at position 3 (oxazepam and 3-hydroxypropoxazepam) showed less effect, which may be due to their ability to bind to BSA. The polarizability of the molecule of 1,4-benzodiazepine derivatives has a greater effect on their binding to BSA and the manifestation of their protective effect than lipophilicity, which suggests a significant contribution of induction interaction in the process of binding to serum albumin.Serum albumin plays an important role in many physiological processes and has recently been shown to be directly involved in the anti-inflammatory processes. Many nonsteroidal anti-inflammatory drugs, in particular, have a protective effect against thermal denaturation of serum albumin. The aim of the work was studying of the in vitro anti-inflammatory activity of propoxazepam and a number of 1,4-benzodiazepine derivatives based on the protective effect on the stability of serum albumin under thermal denaturation. The protective effect of the compounds was expressed as IC50, physicochemical parameters were calculated using the programs ACD/Labs 12.01 and Chem Axom (Marvin Sketch 21.7). The IC50 values for diazepam and propoxazepam were found to be almost twice as high as the reference drug ibuprofen. Compounds with the free hydroxy group at position 3 (oxazepam and 3-hydroxypropoxazepam) showed less effect, which may be due to their ability to bind to BSA. The polarizability of the molecule of 1,4-benzodiazepine derivatives has a greater effect on their binding to BSA and the manifestation of their protective effect than lipophilicity, which suggests a significant contribution of induction interaction in the process of binding to serum albumin.